2sqrt(28)3sqrt(63)-sqrt(49)

<-- Enter expression

Evaluate 2√283√63-√49

Term 1 has a square root, so we evaluate and simplify:
sqtot = 2
We have a product of 2 square root terms
The product of square roots is equal to the square root of the products
2√283√63 = 2√28*63
2√283√63 = 2√1764
Simplify 2√1764.

If you use a guess and check method, you see that 412 = 1681 and 432 = 1849.
Since 1681 < 1764 < 1849 the next logical step would be checking 422.

422 = 42 x 42
422 = 1764 <--- We match our original number!!!
Multiplying by our outside constant, we get 2 x 42 = 84
Therefore, 2√1764 = ±84

Term 2 has a square root, so we evaluate and simplify:
Simplify -1√49.

If you use a guess and check method, you see that 62 = 36 and 82 = 64.
Since 36 < 49 < 64 the next logical step would be checking 72.

72 = 7 x 7
72 = 49 <--- We match our original number!!!
Multiplying by our outside constant, we get -1 x 7 = -7
Therefore, -1√49 = ±-7

Group constants
84 - 7 = 77


Build final answer:
77